Girl, talk : a campaign empowering female undergraduates to respond to campus sexual harassment - Chim, Danelia Xin Yi (Nanyang Technological University, 2020)
Girl, Talk was a digital-first campaign empowering female undergraduates in Singapore to respond to campus sexual harassment (CSH). With an agent-centric strategic approach, the campaign achieved a significant 134% increase in meaningful conversations about CSH and a PR value of S$504,000. Studies on sexual harassment and assault have shown that actively responding to harassment decreases the emotional trauma borne by the victim in harassment incidents. Underpinned by this knowledge, Girl, Talk is distinguished from existing anti-harassment campaigns by its agent-centric perspective which encouraged female undergraduates to take agency. By increasing their knowledge of how to respond and confidence in responding, the campaign aimed to increase the average of meaningful conversations by female undergraduates about CSH. Framed by the theory of Sensemaking and the Knowledge-Attitude-Behaviour model, key research findings surface socio-cultural and physiological barriers to responding, and targeted messaging through digital media platforms as the most effective in helping our target group overcome these barriers. The campaign utilised these findings to develop the pillars “Recognise” and “Respond”, strategically distributing its messages across different digital platforms with paid, owned, and earned media. Through its 8-week campaign period, Girl, Talk gained over 16,300 social media engagements and secured 12 pieces of coverage across local, regional and international press.